Medicine and Smart Phones - Kayastha, R (Kathmandu University Medical Journal, 2012)
KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 94 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6925